Meningkatkan Kemampuan Bahasa melalui Bercerita dengan Media Gambar Seri pada Peserta Didik Kelompok B4 TK Negeri Pembina Mataram - Sridawati, Baik (ANWARUL, 2022)
This classroom action research aims to improve language skills through storytelling using picture series media for group B4 students of the Mataram State Kindergarten for the 2021/2022 Academic Year. This classroom action research was conducted at Pembina Mataram State Kindergarten, with the research subjects being students of group B4 with a total of 16 people and the object being language skills. This research was conducted in two cycles consisting of four competencies from each cycle, namely: planning, action, observation and reflection. Data collection techniques through observation data. The results of this study indicate that the use of serial image media can improve language skills through storytelling. This increase can be seen from the average score of students in the first cycle, which is 64.62 to 81.5 in the second cycle. This shows that learning by using picture series media can improve language skills through storytelling to students in the B4 group of the Mataram State Kindergarten.